2019
DOI: 10.1111/ijcp.13336
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment of type 2 diabetes: Its cost is significantly associated with HbA1c levels

Abstract: Aims To examine the relationship between costs of hyperglycaemia drug treatment and glycemic control amongst people with type 2 diabetes (T2D). Methods This observational study utilised data from the QUALIDIAB database on 3,452 T2D patients seen in Diabetes Centers in Argentina. Patients were classified according to their HbA1c value into two groups: on target (OT; HbA1c ≤ 7%), and not on target (NOT; HbA1c > 7%); within each category we considered clinical and metabolic indicators, as well as type of hypergly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
1
0
3
Order By: Relevance
“… References 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 …”
Section: Supporting Informationunclassified
“… References 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 …”
Section: Supporting Informationunclassified
“…A meta-analysis showed that globally, only 42.8% of people achieved optimal HbA1c targets, with Europe and North America showing the best results [ 11 ]. Recent studies found adequate glycemic control rates of 31.8% in Mexico, 53.4% in Colombia, 48.9% in Argentina, and 50.4% and 53.4%, respectively, in men and women in Korea [ 12 15 ]. In Brazil, a study in the southern region showed 30.2% of people enrolled in primary health care (PHC) with adequate glycemic control [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Именно этот уровень признаётся необходимым для достижения в процессе лечения, поскольку при таких параметрах углеводного обмена снижается риск сердечно-сосудистых осложнений (ИБС, острого инфаркта миокарда, острого нарушения мозгового кровообращения и др.) [11,12]. Эти осложнения являются ресурсоёмкими, требующими больших общественных и личных расходов [13].…”
Section: введение / Introductionunclassified